STRATEGY AND PLANNING IN OVERCOMING HOAX ON PHOENIX RADIO BALI - Putri Ekaresty Haes; Sahri Aflah Ramadiansyah; I Putu Dharmawan Pradhana (Journal of Innovation Research and Knowledge, 2024)
The main objective of the study is to reveal the innovations in the planning and communication strategies used by Phoenix Radio Bali in dealing with fake news among Generation Z. The study uses three methods data collection, observation of participants, in-depth interviews, and documentation. The research uses qualitative methods with a case study approach. Based on the results of the research, Phoenix Radio Bali uses strategic planning and communications in delivering the message to listeners initiated by Phil Jones through five stages, namely the launch of strategy, planning, and planning of strategy implementation, strategy analysis and planning, strategy follow-up, and commitments, and the final stage is the implementation of the plan and monitoring of its results. Phoenix Radio Bali has managed to maintain its presence in the digital age, despite the prevalence of fake news and fraud. The success of the radio station can be attributed to its staff's commitment to reporting news based on data and facts, and ensuring that all news broadcasts are thoroughly tested facts before reaching its listeners, the Z generation.